2011
DOI: 10.1002/asi.21492
|View full text |Cite
|
Sign up to set email alerts
|

Not just information: Who searches for what on the search engine Google?

Abstract: This paper reports on a transaction log analysis of the type and topic of search queries entered into the search engine Google (Australia). Two aspects, in particular, set this apart from previous studies: the sampling and analysis take account of the distribution of search queries, and lifestyle information of the searcher was matched with each search query. A surprising finding was that there was no observed statistically significant difference in search type or topics for different segments of the online po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 35 publications
0
35
0
1
Order By: Relevance
“…Another approach is to use aggregate ranking sites such as Alexa (http:// www.alexa.com/ ), but otherwise little is publicly known about who uses the web in general. Two exceptions are Waller (2011) who has examined information seeking by Australians, and Segev and Ahituv (2010) who provide a more global perspective. Wu and Taneja (2016) have more recently contributed to our understanding of attention paid to the world's top websites by grouping them by format and genre and in terms of their popularity.…”
Section: Online Information In Everyday Lifementioning
confidence: 99%
“…Another approach is to use aggregate ranking sites such as Alexa (http:// www.alexa.com/ ), but otherwise little is publicly known about who uses the web in general. Two exceptions are Waller (2011) who has examined information seeking by Australians, and Segev and Ahituv (2010) who provide a more global perspective. Wu and Taneja (2016) have more recently contributed to our understanding of attention paid to the world's top websites by grouping them by format and genre and in terms of their popularity.…”
Section: Online Information In Everyday Lifementioning
confidence: 99%
“…Yet studies suggest that the vast bulk of Google searches are for consumption, with only a tiny proportion (1-2 per cent) devoted to political information and other 'serious' types of information. Even more surprisingly, what people search for is very similar across the world, and cuts across how populations are stratified in terms of economic and status groups (Waller 2011a). The implication is that it is important to focus on the small proportion of information for political, health, education and research -or what I will single out as 'serious' -uses.…”
Section: Chapter Overviewmentioning
confidence: 99%
“…A different approach is quantitative, and we have already encountered the study of search engine use in Australia (Waller 2011a), which found that the vast bulk of content sought relates to consumer activity and popular culture. In the light of the distinction between serious and non-serious information that has just been made, it can be mentioned that less than 2 per cent of search queries in Waller's study related to 'serious information' such as civic, health and political information.…”
Section: The Web Of Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is substantial evidence of the use of search engines on the Internet as a widely used, indeed, primary mechanism for finding information (Waller, 2011), and Google's dominance among search engines is well established (Google has 80.9% of market share, according to StatOwl) 2 . As early as 2007, studies showed the prevalence of Google in academic use of the Internet across a range of disciplines (Nicholas, 2007).…”
Section: Why Google Searches?mentioning
confidence: 99%